Empowering Housewives in Improving Family Health Through Manufacturing Training Traditional Herbal Drink - Andy Hayun Abidin; Mujito Mujito; Ning Arti Wulandari (Journal of Community Service for Health, 2026)
The transformation of the health system is focused on comprehensively addressing health problems and strengthening disease prevention. Traditional drinks in Indonesia are known as "jamu" which have long been made and consumed as a drink for relaxation and refreshment and are believed to be beneficial for health for generations. The purpose of this activity is to increase public knowledge about family medicinal plants and improve the skills of housewives in making herbal drinks to improve health and family economy. The training was conducted using lecture and demonstration methods by the presenters and continued with direct demonstrations by the participants. The materials provided were the concept of traditional drinks made from natural herbs, various techniques for making natural herbal drinks and the use of natural herbs, techniques for making traditional drinks and techniques for packaging traditional drinks, procedures for managing Household Industry Food Permits and the formation of herbal drink maker groups. Evaluation of activities to increase knowledge and skills in making herbal drinks was 46.4%. This community service activity, in addition to improving participants' skills in improving health, also improves the family economy, so it is necessary to continue with the provision of materials on product packaging and marketing through digital media to improve marketing.